Influence of the height of the mandibular ridge on the masticatory function during the functional adaptation with new complete dentures (Journal of Applied Oral Science, 2021)
The period of functional adaptation to a new conventional complete denture embraces many transitory issues, and this period is directly related to the rehabilitation success. Objective: This clinical trial evaluated the influence of the height of mandibular ridge on the masticatory function of complete denture (CD) wearers during the adaptation period. Methodology: A total of 28 individuals wearing new CDs (NR, n=14, normal mandibular ridges, 64±12.5 years, 9 female; RR, n=14, resorbed mandibular ridges, 69±6.8 years, 9 female) were assessed at 24 hours, 30 days, three months and six months after the insertion of the CDs for masticatory performance (MP, sieves method), satisfaction with CDs (questionnaire) and maximum occlusal bite force (MOBF) (gnatodynamometer). The classification of the mandibular ridges followed the Kapur index. Data of MP and MOBF were analyzed by two-way ANOVA and satisfaction with CDs was analyzed by Generalized Estimating Equations (GEE), α=.05. Results: Participants with NR presented better masticatory performance (p=.000 - NR 30.25±9.93%, RR 12.41±7.17%), general satisfaction (p=.047), retention of mandibular denture (p=.001), chewing ability (p=.037), and comfort of wearing a mandibular denture (p=.000). Regardless of the mandibular ridge, MP (p=.000) was higher at three (21.26±12.07%) and six months (24.25±12.26%) in comparison to 24 hours (18.09±10.89%), the MOBF (p=.000) was higher at three months (78.50±6.49 N) compared to 24 hours (57.34±5.55 N) and 30 days (62.72±5.97 N), and the comfort of wearing a mandibular denture (p=.002) at three months (1.61 ± 0.07) was greater than 24 hours (1.29±0.10) and 30 days (1.36±10). Conclusions: The study suggests that the participants with NR have higher MP and satisfaction with their CD, regardless of the follow-up period after the insertion of the new CD. After subjects received the CD, a period of 3 months was necessary for achieving better achievement MOBF, MP, and self-perceived comfort with the mandibular denture, regardless of the height of the mandibular ridge.